The demand for a workers bailout a case study of the Giardini del Sole strike - Velasco, Benjamin B. (Philippine Journal of Labor and Industrial Relations, 2010)
The paper is a study of the first worker's strike against mass retrenchments in the wake of the global economic crisis. The workers of the furniture factory of Giardini del Sole in Mandaue City went on strike in February 2009 after the company laid off more than half of the workforce. In the months after the Giardini strike, labor militancy ratcheted up among Cebu workers. Using the perspective of labor economics, the paper focuses specifically on the workers' demand for a bailout (a higher package of separation benefits than mandated by law) in the face of job losses and loss of income.